(3eYGedGJ GdEQJHGW hGdebGjjS GddGeYdejIs - (3eUWaj MSjf(B, (3HGgjs; (3eMehO YHO GdaJGM YfGf(B, s ((3GdEScfOQjI(B:s (3ecJHI GdCfLdh(B,s, 2001)
(3eJZjQGJ heSJhjGJ GdbjGS,GdEQJHGW Hjf eJZjQjjf cejjf(B-(3GdEQJHGW Hjf eJZjQjf JQJjHjjf(B-(3GdEQJHGW Hjf eJZjQjjf GSejjf(B-(3eYGed GdEQJHGW GdLRFj(B-(3GdEfMOGQ(B-(3GdENJHGQGJ GddGeYdejIs
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s